THE EFFECT OF FISCAL STRESS ON CHANGES IN SOCIAL AID SHOPPING WITH LEGISLATURE SIZE AS MODERATING Empirical Evidence from Regency/City Governments in Sumatra - Sari, Nanda; Abdullah, Syukriy; Maryasih, Lilis (Riset Akuntansi dan Keuangan Indonesia, 2022)
This study aims to examine the effect of fiscal stress (FS) on changes in social assistance expenditure budget (BBS) with legislature size (LS) as a moderator in local governments on the island of Sumatra. The sample used is 154 districts/ cities with purposive sampling technique. Secondary data is taken from local government financial reports which have been audited by the Supreme Audit Agency of the Republic of Indonesia (BPK RI). The analytical method used in this research is Moderated Regression Analysis. The results of this study prove that FS affects changes in BBS and LS has an effect on changes in BBS. However, the LS does not moderate the effect of fiscal stress on changes in BBS.